PENGARUH PEMBANGUNAN NASIONAL TERHADAP PEMBANGUNAN DESA - Firda Nuryani Khoerunnisa (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2018)
In order to enhance public participacion in required development approaches or methods, to increase community participation in the development process from the community itself. Rural development is intended to help rural communities build rural infrastucture and refers to a variety of necessary, or policy measures to be taken by the government in implementing development needs to be placed in a single unit with thw city in order to develop an integrated region. Implementation of rural development is inseparable from the consciousness of every citizen who lives in the village, community participation is a condition that can guarantee the succesfull development of rural development is essentially a procces of modernization that led to the nation, society and the State of Indonesia towards better life ahead.